ByzRev 04.2022.009: Silvia Ronchey, Hypatia. The True Story. : English translation by Nicolò Sassi, with the collaboration of Giulia Maria Paoletti. Berlin – Boston: De Gruyter 2021. - Herrin, Judith (The Byzantine Review, 2022)
Silvia Ronchey, Hypatia. The True Story. English translation by Nicolò Sassi, with the collaboration of Giulia Maria Paoletti. Berlin – Boston: De Gruyter 2021. XV, 268 pp. – ISBN 978-3-11-071757-0 (€ 79.95)